PENGARUH PERPUTARAN TOTAL ASET DAN DEBT TO ASSETS RATIO TERHADAP RETURN ON ASSETS - Hernawati, Euis; Hatimatunnisani, Hani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to determine the effect of total asset turnover and debt to assets ratio on return on assets at PT Waskita Karya Tbk. The author uses a sample, that the company's financial reports in 2015-2019. The examination technique used is the purposive method, in addition to the classical assumption test method, model feasibility test and multiple regression analysis used by the author for data processing. The results showed that return on assets was significantly affected by total asset turnover, and return on assets was not significantly affected by debt to asset ratio. However, the total asset turnover and the debt to assets ratio simultaneously have a significant effect on return on assets.